2012
DOI: 10.1049/iet-com.2012.0141
|View full text |Cite
|
Sign up to set email alerts
|

On eigen-based signal combining using the autocorrelation coefficient

Abstract: In typical signal combining scenarios, the combining weights are estimated using the criterion of maximum average signal-to-noise ratio (SNR) or maximum combined output power (COP). Eigen-based algorithms are very important and popular in signal combining. The conventional SNR EIGEN or COP EIGEN may not necessarily be effective in terms of performance or system complexity. The main contribution of this study is the introduction of the combined signal autocorrelation coefficient as a newer objective function to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…From the view of Figure 2b, with the time length increasing, the oscillation amplitude of the autocorrelation coefficient is decreasing and the oscillation center is approaching the 0 point. After more than 2400 h (100 days), the autocorrelation coefficient maximum value of PV sequence drops below 0.3 [26][27][28], Thus, we can think that correlation between the PV output at any time and PV output historical data changes before 100 days is weak, Energies 2017, 10, 1616 6 of 15 and its influence is very small. Therefore, in the three PV power plant capacity scenarios, it is concluded that we should take 100 days as a time length sample to analyze the PV output data.…”
Section: Output Data Autocorrelation Analysismentioning
confidence: 97%
“…From the view of Figure 2b, with the time length increasing, the oscillation amplitude of the autocorrelation coefficient is decreasing and the oscillation center is approaching the 0 point. After more than 2400 h (100 days), the autocorrelation coefficient maximum value of PV sequence drops below 0.3 [26][27][28], Thus, we can think that correlation between the PV output at any time and PV output historical data changes before 100 days is weak, Energies 2017, 10, 1616 6 of 15 and its influence is very small. Therefore, in the three PV power plant capacity scenarios, it is concluded that we should take 100 days as a time length sample to analyze the PV output data.…”
Section: Output Data Autocorrelation Analysismentioning
confidence: 97%